2020
DOI: 10.1007/s10461-020-02839-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Mitigates Negative Impact of Food Insecurity on Antiretroviral Adherence Among Postpartum Women in Western Kenya

Abstract: Food insecurity (FI), low social support, and low health-related quality of life (HRQoL) are associated with self-reported nonadherence to antiretroviral therapy (ART) among postpartum women, but these relationships have not been evaluated using objective adherence indicators. Hair samples were therefore analyzed among 83 postpartum Kenyan women living with HIV on efavirenz and nevirapine ART drug regimens in an observational cohort (NCT02974972). FI (0-27), social support (0-40), and HRQoL (8-40) in the prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Lack of proper clothing and food insecurity were among the main socioeconomic constraints that negatively affected retention of HIV treatment found in the present study that even got worse in the COVID-19 pandemic. These factors have also been reported in other studies conducted in Togo, Ethiopia and Kenya (Bezabhe et al, 2014;Yaya et al, 2014;Aibibula et al, 2017;Wang et al, 2020). Patients usually lose follow-up when they migrate either within Pakistan or overseas for work purposes (Ahmed et al, 2020b).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Lack of proper clothing and food insecurity were among the main socioeconomic constraints that negatively affected retention of HIV treatment found in the present study that even got worse in the COVID-19 pandemic. These factors have also been reported in other studies conducted in Togo, Ethiopia and Kenya (Bezabhe et al, 2014;Yaya et al, 2014;Aibibula et al, 2017;Wang et al, 2020). Patients usually lose follow-up when they migrate either within Pakistan or overseas for work purposes (Ahmed et al, 2020b).…”
Section: Discussionsupporting
confidence: 59%
“…Some qualitative studies have reported barriers that include forgetfulness, fatigue, hopelessness (Jones et al, 2015), stigma and discrimination (Wasti et al, 2012), HIV non-disclosure (Arnold et al, 2014), and religious beliefs (Holtzman et al, 2015;Medved Kendrick, 2017). Facilitators of retention to treatment include family support (Yehia et al, 2015), positive relationship with healthcare providers (Nam et al, 2008), access to affordable transportation (Yehia et al, 2015), livelihood support (Wang et al, 2020), improved knowledge about the disease (Ammon et al, 2018), reminders (Nam et al, 2008), attending a support group (Wang et al, 2020), and carrying ART while away from home (Kumarasamy et al, 2005;Croome et al, 2017). Many of the reported barriers and facilitators are implicated in the Pakistani context; however, some may be unique and not reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Household wealth was derived using a principal components analysis of a household's ownership of assets and dwelling characteristics (roof materials, sanitation facilities) using methods from the Demographic and Health Surveys [33]. Household food insecurity in the prior 30 days was based on the 9-item Household Food Insecurity Access Scale (range: 0-27) [12], a measure that has been crossculturally validated and previously used among adults living with HIV in Kenya [6,[34][35][36].…”
Section: Covariatesmentioning
confidence: 99%
“…Social support or interpersonal support is defined as the existence or availability of people who let an individual know that they care about, value, and love them [14]. Perceived social support contributes to retention in HIV care, ART adherence and general wellbeing of nursing mothers living with HIV [15,16]. Postpartum period and HIV are two medically independent complex phenomena.…”
Section: Introductionmentioning
confidence: 99%